Research on Visual Teaching Strategy of Chemical Declarative Knowledge in Middle School - Jia, Tianmeng; Wang, Chenyu; Sun, Lin (Advances in Social Sciences Research Journal, 2023)
The rapid development of information technology has a strong impact on the traditional chemistry teaching mode. According to the teaching status of Chinese middle school chemistry classroom, the thesis combines declarative knowledge and visual teaching in junior high school chemistry textbooks as a subject for in-depth research. By elaborating the concepts of declarative knowledge, knowledge visualization and visual teaching, taking knowledge classification theory, visual thinking theory, double coding theory and information processing theory as the research basis, this paper deeply analyzes and summarizes the chemical declarative knowledge and visual teaching methods, and puts forward feasible visual teaching strategies to promote students to master knowledge and develop ability. According to the research and design of the teaching case of the section "Solubility" in the junior high school chemistry textbook, the purpose of this teaching case is to improve the teaching mode, help students understand and build a new system of knowledge, and cultivate students’ innovation ability and core accomplishment of the subject.